The Ideology of Hatred : The Psychic Power of Discourse - Yanay, Niza (Book collections on Project MUSE., 2012)
The twenty-first century might well be called the age of hatred. This is not because there is more violence in the world but because hatred has been transformed from a concept perceived to be a by-product of personal or collective violence into a discursive field. But what if longstanding antagonisms, especially those between social groups, turned out to involve desire rather than revulsion? The Ideology of Hatred develops a psychosocial framework for understanding this new phenomenon by interrogating unconscious mechanisms within national discourse. It opens new and timely venues for thinking about the paradoxes of love and hate, while raising questions about social attachment and otherness. Is it possible that hatred operates by maintaining a safe closeness, enhancing the illusion of separateness as well as a sense of proximity at one and the same time? Could it be that love actually survives through the discourse of hatred as an invisible relation of attachment, necessary but unthinkable? In addition to its strong theoretical component, the book is also based on extensive empirical research, especially into hate relations among Jews and between Jews and Palestinians in Israel.